Determination of acceptance criteria for prestressing strand in pre-tensioned applications - Polydorou, Thomaida (Kansas State University, 2014)
ASTM recently adopted the Standard Test Method for Evaluating Bond of Seven-Wire Steel Prestressing Strand as ASTM A1081, a pull-out test procedure developed for verifying the ability of steel strands to bond to cementitious materials prior to their use as tensile reinforcement in prestressed concrete sections. The required by ASTM International precision and bias statement has not been developed for this test method. In addition, a minimum threshold value that will ensure only adequately bonding strand sources will be accepted has not yet been applied to ASTM A1081. The test method was developed after findings that prestressing steel strand sources of identical type and grade vary significantly as far as their bonding capacity. Bond is a crucial aspect of the prestressing force being transferred into the concrete, and insufficient bonding action can result in the prestressed concrete section lacking in capacity to sustain the loads that it was designed for. After an initial survey of the pull-out strength of North American Strand in mortar, three strands of differing pull-out strengths were selected for inclusion in further testing. A precision and bias statement for ASTM A1081 was developed by first performing ruggedness testing to determine how the results are affected by allowable variations in methods and materials, and followed by an inter-laboratory study to determine the reproducibility of the test method. Once the precision and bias statement for the standard test method was developed, the same strand sources were tested for their performance in concrete beams. Statistical analysis of the flexural beam testing data and correlation with the prestressing strand sources’ ASTM A1081 test results was performed, and the industry was provided with minimum acceptance criteria for prestressing strand tested by ASTM A1081, along with recommendations regarding the standard test method and aspects of prestressed concrete design.
Keywords: Prestressed Concrete; Prestressing; Strand; Strand Bond; Pullout Test; Civil Engineering (0543)